1998
DOI: 10.2134/agronj1998.00021962009000030014x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing DCPA Losses in Furrow Irrigation by Herbicide Banding and Straw Mulching

Abstract: There are concerns about residues of DCPA (dimethyl 2,3,5,6‐tetrachloro‐1,4‐benzenedicarboxylate) and its two acid metabolites in surface runoff from furrow‐irrigated croplands. We studied the effects of mulching irrigation furrows with wheat (Triticum aestivum L.) straw on DCPA movement in runoff solution, with sediment, and in the soil profile. The study site had a Nyssa silt loam (coarse‐silty, mixed, mesic Xerollic Haplodurid) with a 3% slope. The field was planted to onion (Allium cepa L.) and was furrow‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Thus, information is needed about optimal soil water contents, crop water requirements and water use of drip-irrigated crops. A number of studies have been done for furrow-irrigated crops (Smith and Freney 1998;Shock et al 1998;Yin et al 2000) but very few for drip-irrigated dense crops (Shock et al 2005). The major crop in north and northwest China is wheat, which is a dense crop.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, information is needed about optimal soil water contents, crop water requirements and water use of drip-irrigated crops. A number of studies have been done for furrow-irrigated crops (Smith and Freney 1998;Shock et al 1998;Yin et al 2000) but very few for drip-irrigated dense crops (Shock et al 2005). The major crop in north and northwest China is wheat, which is a dense crop.…”
Section: Introductionmentioning
confidence: 99%
“…DCPA metabolites, however, were found in shallow aquifers underlying parts of the intensively farmed areas of Malheur County, Oregon (Bruch 1986;Parsons and Witt 1988). Due to concerns about residues of DCPA and its metabolites in surface water and sediment runoff from furrow-irrigated crop land, as well as through deep percolation through the soil profile, MES conducted intensive studies to trace the fate of DCPA and DCPA metabolites' with both banding and broadcast DCPA application techniques (Shock et al 1998e).…”
Section: Transformations In Agricultural Chemical Usementioning
confidence: 99%
“…Shock et al . () reported that 0.9 t straw/ha applied to irrigation furrows substantially reduced soil erosion by 95%, run‐off by 43%, N losses by at least 50% and 15‐fold for P losses in sediment.…”
Section: Discussionmentioning
confidence: 99%